Polytetrafluoroethylene modifying: A low cost and easy way to improve the H2O resistance ability over MnOx for low-temperature NH3-SCR. Issue 3 (June 2019) - Zhang, Ningqiang; Li, Lingcong; Zhang, Bingbing; Sun, Yanming; Song, Liyun; Wu, Rui; He, Hong
Graphical abstract: Highlights: MnOx and PTFE composite materials were prepared for the first time. Mn-PTFE showed a better H2 O resistance ability compared with MnO2 and Mn2 O3 in low-temperature SCR. Hydrophilic surface could lowering the probability of surface active sites consumed by H2 O and SO2 . Abstract: Herein, an easy and low cost way is proposed to improve the H2 O resistance ability of MnOx catalyst for low-temperature selective catalytic reduction (SCR), via PTFE modifying. The introduction of PTFE to MnOx promoted more tightly packed nanowires, generating a more hydrophobic surface. Mn-PTFE catalysts displayed H2 O and SO2 resistance, lowering the probability of surface active sites being consumed. This work provides a new insight into the design of novel Mn-based composite catalysts with H2 O and SO2 resistance ability, as well as promoting practical applications of Mn-based catalysts in low temperature SCR.